Heavy metals in bitter gourd (Momordica charantia): human health risk assessment - Yap, Chee Kong; Yaacob, Aziran; Ibrahim, Mohd Hafiz; Nulit, Rosimah; Leow, Chee Seng (ARC Publications, 2019)
Momordica charantia (bitter gourd) were collected between May and December 2016 from Kg. Ara Kuda (Penang), Kuala Ketil (Kedah) and Sg. Rengat, Jerantut (Pahang) of Peninsular Malaysia. The metal concentrations (mg/kg dry weight) the edible fruity bitter gourd ranged from the three farming sites were8.00-16.1 for Cu, 46.0-118 for Fe, 0.18-1.98 for Ni, 0.79-1.46 for Pb and 17.2-46.8 for Zn. For the human health risk assessment via consumption of the bitter gourds, all the target hazard quotient values for Fe, Cu, Ni, Pb, and Zn were below 1.00. This indicated that there were no non-carcinogenic risks of Fe, Cu, Ni, Pb, and Zn via the consumption of bitter gourds from the three farming sites. However, it is still advisable that regular monitoring of heavy metals in the bitter gourds be conducted in order to check for possible toxicological risks of the bitter gourd consumption.